ISLAM IN THE JAVANESE CULTURAL PLURALISM AND THE KERATON PERFORMING ARTS - K.R.T. Sunaryadi Maharsiworo (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
The religion of Islam as new religion in the 15th century managed to internalize in the religious and cultural field of Javanese society peacefully. The religion was easily accepted because all its teachings are based on a search of “sangkan paraning dumadi” and promote “Manunggaling kawula lan Gusti” as in principles of the Javanese human life. The concept of kewalian, the mysticism and the concept of perfection of life could be applied in the formulation of the Keraton (Javanese Sultan’s Palace) which became a model of the traditional conception of a variety of social rules and rituals, so that there is mutual interdependence between the Islamic teachings and the community who are still bound by tradition and customary norms. Then various rituals that have been Islamized emerged. Islam was conceived and developed with the Javanese view, absorbed and processed into different forms of Kejawen (Javanese) culture different from the original form, and acceptable to society. In the world of performing arts, needless to say, it has been affected by subculture of Javanese Islam. At least such impressions can be seen in the wayang (Javanese traditional puppetry) performance and ritual dances such as bedaya, wayang wong,or Golek Menak in the Keraton of Yogyakarta. Keywords: Islam, cultural contact, Javanese Philosophy, Dance